Role of Women in Consumption Behaviour: A Comparison of Working and Non Working Wives in Shimla Town - Kathuria, Kapil; Rana, Poonam (Indian Journal of Marketing, 2016)
Women have a significant role in the consumption processes of a family and are an influential marketing segment. The objective of this paper was to compare the roles played by working wives (WW) and non working wives (NWW) of Shimla in consumption of different kind of products the families used. The study is based on a sample of 60 respondents of which 30 were working wives and 30 were non-working wives. The data was collected by using a structured questionnaire dealing with roles played by women in purchase of non durables, durables, and high value products. It was observed that working wives were more active in consumption related roles of high involvement products, while non-working wives were more active in consumption related roles in connection with low involvement products.